Assessment of winter soft and durum wheat varieties for resistance to yellow and dark brown spots. Issue 2 (December 2021) - Shishkin, N; Derova, T; Kovalenko, N; Ivanisov, M; Kononenko, O
Abstract: Winter wheat varieties sown in the Rostov region are characterized by varying degrees of resistance to pests. The size and quality of the wheat harvest are threatened not only by weather conditions, but are reduced by various pathogens, among which yellow and dark brown spots have recently played a large role. Therefore, the aim of the research is to search for sources of resistance among varieties and samples of winter wheat to the causative agents of pyrenophora (Pyrenophora tritici-repentis) and dark brown spot (Cochliobolus sativus). Resistant varieties serve as an ideal factor inhibiting epiphytotics and improving the ecological environment in general. Disease monitoring was carried out in research and production teams of the Federal State Budgetary Scientific Institution Agrarian Research Center "Donskoy". Laboratory research - in the laboratory of mycology and phytopathology of the All-Russian Institute for Plant Protection. The object of research is 226 varieties and samples of winter soft and durum wheat obtained from the department of selection of winter wheat of the Federal State Budgetary Scientific Institution of the ANC "Donskoy". It was established: in laboratory conditions (VIZR), 15 varieties and samples showed high resistance to yellow spot in soft winter wheat of intensive type. In studies on resistance to dark brown spot out of 155 samples of winter soft wheat, no highly resistant ones were found.